Two cycles of recurrent selection in red bean breeding - Menezes Júnior,José Ângelo Nogueira de (2013)
This study was carried out for the purpose of estimating genetic progress after two cycles of recurrent selection in red bean breeding and of obtaining new lines. In cycle zero, F3:5 and F3:6 families were evaluated. In cycle one, the families were extracted in generation F5 and evaluated in generations F5:6 and F5:7. As the families were evaluated in different years and generations, the estimate of genetic progress was obtained by simultaneously evaluating the 30 best lines obtained at the end of each cycle in experiments conducted through three crop seasons. After two cycles of recurrent selection, genetic progress, in the mean value of the crop seasons, was 7.5% for grain yield, 7% for grain appearance, 33.4% for resistance to rust and 13.2% for resistance to angular leaf spot. Lines of red beans were obtained with potential for being included in future Value for Cultivation and Use (VCU) testing for Minas Gerais, Brazil.